FASE EKONOMI KOREA SELATAN MENUJU TINGGAL LANDAS DAN FAKTOR-FAKTOR PENDUKUNGNYA - Azwirda Aziz; Hamdi Nur; Atik Budi Paryanti (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACT: Korea was one of the poorest countries in the world in the 1960s. However, by 1995 South Korea had become the 11th largest economy in the world. South Korea's phenomenal economic growth is also known as the "Miracle on Han River" (the Han river is a river that flows across the capital Seoul). Indonesia and South Korea have almost the same start of economic development with the per capita income of the population which is also almost the same but with different achievements. There is a contrast between the economic success of these two countries as seen in the GDP per capita of the two countries which is much different. This study aims to find out what policies they have implemented, what development models they have implemented and what factors influence it. Next, compare the economic development of Indonesia with that of Korea to see more clearly the lessons that can be drawn in developing the country's economy. This research is a library study. The results of the research show 1. South Korea's industrialization policy is carried out consistently while Indonesia is inconsistent 2. South Korea is poor in natural resources while Indonesia is rich in natural resources. The lack of natural resources has made them carry out ambitious industrialization policies by gradually developing heavy industries and hi-tech industries. Therefore, the path taken is to limit foreign investment, protect local industries and strengthen them so that they can compete for exports. Meanwhile, Indonesia, which is rich in natural resources, invites foreign investment in natural resource extraction and exports based on natural resources, but forgets to develop a competitive industry. Keyword: economic growth, development models, foreign investment,